Two-dimensional Cr-based ferromagnetic semiconductor: Theoretical simulations and design - Tu, Yufei; Liu, Qingquan; Hou, Lipeng; Shi, Puyuan; Jia, Chaobin; Su, Jingjuan; Zhang, Jiawen; Zhang, Xiuyun; Wang, Bing (Frontiers in Physics, 2022)
Two-dimensional (2D) material is the promising for next-generation information technology. The recently discovered intrinsic magnetic crystals have simulated a renaissance in 2D spintronics, which provides an ideal platform for exploring novel physical phenomena. However, current experimental trial-and-error methods in discovering new spintronic material are still very expensive and challenging. In contrast, based on well-developed first-principles calculations, computationally designing the spintronic materials provide a more efficient way for exploring new ferromagnetic (FM) materials and understanding the nature of magnetic properties. Several predictions, such as CrI3 monolayer, CrGeTe3 bilayer, CrSBr monolayer, FeCl2 monolayer, and Fe3GeTe2 monolayer have been confirmed by experiments, showing the great performance of computational approaches. This minireview article attempts to give a brief of discovering intrinsic 2D spintronics from theoretical aspect, and in particular, we emphasize roles played by calculation based on first-principles methods in designing 2D FM materials and devices. The current challenges and proposals on future developments of 2D spintronics are also discussed.